Studying the Residual Effect of Zeolite and Manure on Alfisols Cation Exchange Capacity and Green Bean Yield - Ahmad Yazid Fudlel; Slamet Minardi; Sri Hartati; Jauhari Syamsiyah (Universitas Sebelas Maret, 2019)
Nowadays the innovations in organic agriculture systems continue to be developed to achieve a sustainable agriculture system. In Indonesia with high rainfall, nutrient loss is still a major problem. The application of zeolite and manure as a soil amendment is expected to increase nutrients available in soil and cation exchange capacity of the soil in the long term. The results on the first planting season showed a significant increase in chemical soil fertility. The objective of this study is to research the effect of residue zeolite and manure on soil chemical fertility and yields of the second planting season. This study used a complete randomized block design. The factors were a dose of zeolite (Z1: 2.5 tons ha -1; Z2: 5 tons ha-1) and kind of manure (P1: quail manure; P2: cow manure), with three replications. The result showed that zeolite treatment of 5 tons ha-1 and cow manure increased the total N soil by 27.78% and 45.4% compared to the control. The treatment of quail manure increased soil organic matter 78.78% compared to the control. The treatment of cow manure increased the green bean yield 28.76% compared to the control.